2014
DOI: 10.1128/jvi.00722-14
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Repression of Epstein-Barr Virus and Kaposi's Sarcoma-Associated Herpesvirus Lytic Cycles by Short- and Medium-Chain Fatty Acids

Abstract: The lytic cycles of Epstein-Barr virus (EBV) and Kaposi's sarcoma-associated herpesvirus (KSHV) are induced in cell culture by sodium butyrate (NaB), a short-chain fatty acid (SCFA) histone deacetylase (HDAC) inhibitor. Valproic acid (VPA), another SCFA and an HDAC inhibitor, induces the lytic cycle of KSHV but blocks EBV lytic reactivation. To explore the hypothesis that structural differences between NaB and VPA account for their functional effects on the two related viruses, we investigated the capacity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 88 publications
1
42
0
Order By: Relevance
“…Moreover, anti-inflammatory responses can be induced by the generation of regulatory T cells through the production of short-chain fatty acid (SCFA) by bacteria belonging to the clostridia cluster [44][45][46]. Also, and perhaps even more important, SCFA, such as sodium butyrate and valproic acid, that act as histone deacetylase (HDAC) inhibitors, can reactivate KSHV [21,22], and therefore increased butyrate production, might promote KS tumorigenesis through lytic activation of KSHV [47]. Interestingly, HIV-infected individuals with severe periodontal disease display a higher level of SCFA in the saliva compared to healthy individuals [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, anti-inflammatory responses can be induced by the generation of regulatory T cells through the production of short-chain fatty acid (SCFA) by bacteria belonging to the clostridia cluster [44][45][46]. Also, and perhaps even more important, SCFA, such as sodium butyrate and valproic acid, that act as histone deacetylase (HDAC) inhibitors, can reactivate KSHV [21,22], and therefore increased butyrate production, might promote KS tumorigenesis through lytic activation of KSHV [47]. Interestingly, HIV-infected individuals with severe periodontal disease display a higher level of SCFA in the saliva compared to healthy individuals [48].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pathogenic mechanisms, including the production of genotoxic inducers, the activation of TLRs and pro-inflammatory pathways, the inhibition of the immune response, and the increase of the cellular turnover have been proposed to explain the oncogenic properties of some types of bacteria [15]. Bacterial byproducts such as short-chain fatty acids (SCFA) that are highly abundant in individuals suffering from periodontal disease can induce KSHV reactivation [21,22]. Interestingly, HIV-infected individuals display a higher rate of periodontal disease [23], which has been proposed to promote oral KS development by inducing proinflammatory cytokines or releasing SCFA.…”
Section: Introductionmentioning
confidence: 99%
“…Epstein–Barr virus reactivation can be triggered in human cells by either chemical agents or biological stimuli, including TPA, sodium butyrate, HDAC inhibitors, phorbol esters, calcium ionophores, chemotherapeutic agents, BCR engagement, TGF-β, and hypoxia ( Figure 1 ; Gorres et al, 2014; Kenney and Mertz, 2014). BCR signaling-mediated EBV reactivation is mainly induced through PI3K and PKC that further regulate the activity of the Zp promoter (Goswami et al, 2012).…”
Section: The Switch Of Lytic Infection and Latencymentioning
confidence: 99%
“…A recent study has shown that reactivation can be induced by some short-chain fatty acids (SCFAs) such as phenylbutyrate through inhibiting histone deacetylase (HDAC) activities (Gorres et al, 2014). Consistently, Yu et al have found that several SCFAs produced by periodontal pathogens such as Porphyromonas gingivalis and Fusobacterium nucleatum can also induce the KSHV lytic reactivation by suppressing HDACs as well as two histone N-lysine methyltransferases (HLMTs): enhancer of zeste homo-log2 (EZH2) and suppressor of variegation 3-9 homo-log1 (SUV39H1) (Yu et al, 2014).…”
Section: Role Of Lipids In Kshv Reactivation and Lytic Replicationmentioning
confidence: 99%